A comparative evaluation of analgo‐sedative effects of oral dexmedetomidine and ketamine: a triple‐blind, randomized study. Issue 12 (25th July 2014) - Singh, Charanjeet; Pandey, Ramesh K.; Saksena, Anil K.; Chandra, Girish; Cote, Charles
Summary Background Use of sedative agents for difficult to manage children during dental procedures has been indicated for years, but neither the agent nor the route has been found to be ideal. Objectives The aim of the study was to evaluate and compare the efficacy and safety of oral dexmedetomidine (D) and ketamine (K) in producing moderate sedation among uncooperative pediatric dental patients. Methods This prospective, triple‐blind, randomized comparative study included 112 ASA grade I children of both sexes aged 3–10 years, who satisfied all the inclusion criteria. They were randomly divided into four groups and ketamine 8 mg·kg−1 (K) or dexmedetomidine 3 μg·kg−1 (D1), 4 μg·kg−1 (D2) and 5 μg·kg−1 (D3) were given orally. Similar dental procedures were performed in these patients, and effects of these drugs were assessed in terms of changes in vital signs, onset and duration of sedation, analgesia, and amnesia. Secondary outcomes such as level of sedation, behavior, adverse effects, and overall success were also measured. Results The onset of sedation was significantly rapid with K and D3 as compared to D1 and D2. Recovery from sedation was fastest in group D1. Intra‐ and postoperative analgesia and anterograde amnesia were highest with K and least with D1, while D3 produced analgesia comparable to K. In K treated group, vomiting was observed in five patients and two patients exhibited emergence phenomenon. Overall, highest success rate was observed in D3 group. Conclusions Given by oral route, the novel sedative dexmedetomidine provides dose‐dependent effective analgo‐sedation, comparable to ketamine, with less adverse effects.